PENGUKURAN KINERJA INSTALASI FARMASI RUMAH SAKIT ADVENT MANADO DENGAN METODE BALANCED SCORECARD PADA PERSPEKTIF KEUANGAN DAN PERSPEKTIF PROSES BISNIS INTERNAL - Malara, Jeril Riski; Citraningtyas, Gayatri; Datu, Olvie S. (UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTHospital Pharmacy Installation (HPI) was a medical support service that was required to provide quality pharmaceutical services to the public, so it requires performance measurement. The purpose of this study was to determined the performance of HPI Advent Manado using the Balanced Scorecard (BSC) method through a financial perspective and an internal business process perspective. This research was a non-experimental, descriptive type of research with retrospective and prospective data collection in the form of primary data and secondary data. The results showed the performance of HPI Advent Manado from a financial perspective in 2019 obtained an Inventory Turn Over Ratio (ITOR) value of 5.53 times and a Gross Profit Margin (GPM) of 22.24%. Internal business process perspective with dispensing time for non-concocted prescriptions 14.47 minutes and concocted prescriptions 28.19 minutes, drug availability 93.30% and drug information services stilled not meeting the standards of Permenkes No.72 of 2016. From the research results it can be concluded that the performance of HPI Advent Manado using the BSC method shows a fairly good performance from a financial perspective, although there was still needed for improvement in the ITOR value, and the internal business process perspective has shown good performance and there was still needed for improvements in drug information services. Keywords: Performance measurement, Pharmaceutical installation hospital, Balanced scorecard, Financial perspectives, Internal Business perspectives ABSTRAKInstalasi Farmasi Rumah Sakit (IFRS) merupakan pelayanan penunjang medis yang dituntut memberikan pelayanan kefarmasian yang berkualitas kepada masyarakat, sehingga memerlukan pengukuran kinerja. Tujuan penelitian ini untuk mengetahui kinerja IFRS Advent Manado dengan metode Balanced Scorecard (BSC) melalui perspektif keuangan dan perspektif proses bisnis internal. Penelitian merupakan jenis penelitian non eksperimental bersifat deskriptif dengan pengumpulan data secara retrospektif dan prospektif berupa data primer dan data sekunder. Hasil penelitian menunjukkan kinerja IFRS Advent Manado pada perspektif keuangan tahun 2019 memperoleh nilai Inventory Turn Over Ratio (ITOR) sebesar 5,53 kali dan Gross Profit Margin (GPM) sebesar 22,24%. Perspektif proses bisnis internal dengan dispensing time untuk resep non racikan 14,47 menit dan resep racikan 28,19 menit, ketersediaan obat 93,30% dan pelayanan informasi obat masih belum memenuhi standar Permenkes No.72 tahun 2016. Dari hasil penelitian dapat disimpulkan bahwa kinerja IFRS Advent Manado dengan metode BSC menunjukkan kinerja yang cukup baik dari perspektif keuangan, walaupun masih perlu upaya perbaikan pada nilai ITOR, dan perspektif proses bisnis internal sudah menunjukkan kinerja baik dan masih perlu adanya perbaikan pada pelayanan informasi obat.Kata kunci: Pengukuran Kinerja, IFRS, Balanced Scorecard, perspektif keuangan, perspektif proses bisnis internal